La evolución de la pobreza difusa multidimensional en México, 1994-2006 - Eduardo Morales Ramos (Banco de México, 2009)
– This article applies fuzzy set theory to measure three dimensions of poverty in Mexico: monetary poverty, non-monetary poverty of private goods and non-monetary poverty of public goods. By using those three dimensions, it is possible to build a joint membership to classify poverty in manifest, latent and non-poverty, which are computed for the three types of official poverty used in Mexico, for urban and rural areas and for the total of households and individuals in Mexico from 1994 to 2006. Moreover, confidence intervals are calculated for each estimation, which are used to establish if there are statistically significant changes along time. Results show that, although poverty in Mexico has diminished between 1994 and 2006, its evolution has been different according to the area and the type of poverty analyzed.
Keywords: I32; 330; multidimensional fuzzy poverty; monetary poverty; non monetary poverty; manifest poverty; latent poverty; Armut; Mexiko